Integrated photonic devices for realizing photonic quantum computing: part 2, FDTD (component-level) - Rayyan Assafi (Nanyang Technological University, 2024)
Starting from 1960s, the development of Light Detection and Ranging (LiDAR) has been rapid. From mechanical sensing LiDAR to now non-mechanical sensing LiDAR which promises a better response time and higher reliability. This project focuses on Optical Phased Arrays in non-mechanical LiDAR. Reviewing and understanding common Optical Phases Array (OPA) waveguide components and its designs would be done in this project. The objective of this project is to create a toolbox for the creation and design of such devices. This toolbox that is being developed for this project has a goal of simplifying the waveguide designing process via the software Ansys Lumerical FDTD . This project will focus on building up the toolbox via Ansys Scripting. Choices such as waveguide material, grating material and its parameters such as etch depth will be available to the user via this toolbox. Overall, the idea is to allow the user to design, simulate and test the design of their devices with relative ease.